Analysis of the Impact of Globalization on International Trade - Bernando Aldo Yosua Tambunan; Putri Ananda; Eka Saripa Br. Siburian; Khairani Alawiyah Matondang; Riza Indriani (International Journal of Business and Applied Economics, 2022)
Through international trade activities, it will be formed connection each other dependency Among countries which there is in world this, where something country may need commodities that cannot be produced independently in their country but are owned by other countries. This research was conducted with the aim of knowing and explaining "Analysis impact Globalization To Trading International." Study this is study normative or literature study that is with examine various leterators with techniques Analysis qualitative analysis data, namely "by describing the data qualitatively in the form of sentences as well as statement for make it easy read and understand data. The results of the analysis can be known factors which influential to trading international and impact Globalization against Trade International, including the presence of Multinational Corporations (MNC). role urgent in international trade and investment world as well as could known impact good character positiv nor negative international trade.